Obstructive sleep apnea: What is an orthodontist's role? - Robert H. Kazmierski (SpringerOpen, 2024)
Abstract Background The American Association of Orthodontists white paper on obstructive sleep apnea and orthodontics remains the most authoritative statement on the topic. This was produced in 2019 due to increasing orthodontic interest in obstructive sleep apnea (OSA) and the lack of formal guidelines for orthodontists. Since the white paper's release, advocacy for contrarian ideas and practices remain. Orthodontists are sometimes acting as primary care providers for OSA. Procedures appropriate only for screening are sometimes being used for diagnosis. The side effects of effective treatments such as mandibular advancement devices need further consideration. Also, research has clarified the effectiveness and ineffectiveness of treatments such as palatal expansion. Results Part of an orthodontist's role is screening for OSA. The correct action when this is suspected remains referral to the appropriate physician specialist for diagnosis and treatment or coordination of treatment. Orthodontists may participate in the treatment of patients with OSA as a member of a multi-disciplinary team. Effective orthodontic treatments may include orthognathic surgery with maxillomandibular advancement and mandibular advancement devices. The negative effects of the latter make this a choice of last resort. Current research indicates that OSA alone is not sufficient indication for palatal expansion. Conclusions Orthodontists should appropriately screen for obstructive sleep apnea. This may be done as part of our health histories, our clinical examination, and review of radiographs taken for purposes other than the diagnosis and screening for OSA. Orthodontic treatment for OSA can be helpful and effective. However, this may be done only after referral to the appropriate physician specialist, as part of a multi-disciplinary team, with consideration of the likely effectiveness of treatment, and after all likely and potential negative consequences have been considered and thoroughly discussed with the patient.